2008
DOI: 10.1121/1.2968686
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychometric-function slopes for forward-masked tones to investigate cochlear nonlinearity

Abstract: Schairer et al. [J Acoust Soc Am 133, 1560–1573 (2003)] demonstrated that cochlear nonlinearity is reflected in psychometric function (PF) slopes for 4-kHz forward-masked tones. The goals of the current study were to use PF slopes to compare the degree of compression between signal frequencies of 0.25 and 4 kHz in listeners with normal hearing (LNH), and between LNH and listeners with cochlear hearing loss (LHL). Forward-masked thresholds were estimated in LNH and LHL using on- and off-frequency maskers and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(63 citation statements)
references
References 42 publications
3
59
1
Order By: Relevance
“…The Schairer et al [4] model was tested by Schairer et al [4] and later by Schairer et al [5]. The results of those experiments provide a vital context for the present experiments.…”
Section: The Cochlear Compressive Nonlinearitymentioning
confidence: 74%
See 4 more Smart Citations
“…The Schairer et al [4] model was tested by Schairer et al [4] and later by Schairer et al [5]. The results of those experiments provide a vital context for the present experiments.…”
Section: The Cochlear Compressive Nonlinearitymentioning
confidence: 74%
“…The Schairer et al [4] and Schairer et al [5] results suggested that their model could be correct, but were not conclusive. The Schairer et al [4] model can be tested further, using data that reliably document the slopes of the psychometric functions for probetone detection thresholds over a broad range of probe-tone detection thresholds.…”
Section: A Necessary Methodological Prelude: Overview Of the Present mentioning
confidence: 93%
See 3 more Smart Citations